Multifund choices within a lifecycle investment model. The Colombian Case - Gómez Morales, Camilo; Andrade-Valbuena, Nelson A.; Moscoso Durán, Fabio (Estudios de Administración, 2016)
The purpose of this research is to study the welfare impact on consumption that lifecycle investors constrained to make compulsory contributions into a pension fund will get by choosing a multifund. The use of simulation techniques is applied to a life cycle investment model designed to fit the situation of the Colombian private pension system. It shows the importance of combining the percentage of investments in equity in the pension fund with the structure of human capital in order to determine which investment vehicle individuals should be chosen in order to save for retirement.